Dosimetric verification of the Elekta motorized wedge - Behjati, Mahdie; Sohrabpour, Mostafa; Shirmardi, Seyed Pezhman; Bouzarjomehri, Fathollah; Mosleh Shirazi, Mohammad Amin (Archives of Advances in Biosciences, 2018)
Elekta linear accelerator is equipped with a motorized wedge which produces the wedge angles of less than 60° continuously by the combination of a wedged field and an open field with appropriate proportions. The effective wedge angles for various field sizes and depths were calculated using an analytical formula and a 2-D array detector data. The validity of the effective wedge angles has been done by determining wedge angles in accordance with ICRU-24. The effect of the field size on the wedge angle and wedge factor was investigated for motorized wedge. The maximum difference between planned and measured angles was found to be about 10̊. The planned dose for different wedge angles and field sizes compared with measured doses and their differences were found to be less than 3%. The calculating wedge factor throughout linear interpolation method for all field sizes from a few selected measurements had been proved for physical wedge beforehand. This method was applied to obtain the wedge factors with field size and compared with measured data for motorized wedge. The errors were in agreement with ICRU proposed error and less than treatment planning system error. The linear relation between wedge angle and output factor and depth were investigated and the linear interpolation method was proved to calculate wedge angle for any output factor and depth.